Burma at the turn of the twenty-first century - Skidmore, Monique (University of Hawaii Press, 2005)
This is the first study in a half century of one of the least known societies in the contemporary world. Burma at the Turn of the 21st Century provides insight into the everyday lives, concerns, and values of the people of this reclusive nation. Prominent anthropologists and religion scholars with in-depth, long-term knowledge of central Burma offer detailed analyses of the ways in which Burmese actively manage and create lives for themselves in the shadow of a military dictatorship. Their research crosses the domains of religious, political, and social life, examining public festivals and performance, local-state relations, literary life, lottery frenzies, mass meditators, political rumors and black humor, the value of children, changing male identities, and more in this impressive, wide-ranging collection.